Big pharma and the opioid epidemic : from Vicodin to heroin - Braun, Eric, 1971- (Informed! (North Mankato, Minn.), 2020)
Discusses the opioid crisis in the United States and outlines what caused the crisis to progress to the severity it is today. Details the history of opioids and how the cycle of addiction has affected the lives of people of all ages and economic class. Provides information on the response to the opioid epidemic by federal and local politicians, celebrities, and everyday citizens. Includes color photographs, fact boxes, graphs, ways to get involved, a glossary, and additional resources.